PERAN MODAL SOSIAL DALAM MENCAPAI PERUBAHAN SOSIAL DI LEMBAGA PENDIDIKAN ISLAM - Rivaldy, Nurdin; Tihami, Tihami; Gunawan, Agus (Tarbiyatuna Kajian Pendidikan Islam, 2024)
Islamic educational institutions have an important role as the main factor in social change, where the entire life system rests on educational values as the basic foundation. A significant instrument in education is social capital, manifested in the role of human resources with a multifunctional approach that makes the institutions of life become. The study aims to determine the role of Islamic educational institutions in achieving social change with social capital instruments using a structural-functional theory approach. The research method uses qualitative research with a literature study approach sourced from books and journals related to educational and social institutions. The study results illustrate that Parson's paradigm explains structural-functional theory with distinguishing features, adaptation, goal attainment, integration, and latency (AGIL), applied in Islamic educational institutions by reconstructing the roles of educational components and social groups. Strengthening Islamic educational institutions through social capital in which social change occurs will be created through components of trust, networks, norms, and leadership that provide broader benefits for Muslim life. The implications of the research show that structural-functional implementation will provide social change with existing social capital so that the use of Islamic educational institutions serves as a means to involve the younger generation in acquiring knowledge, changing behaviour, and achieving proficiency in the principles governing community participation.